The effects of 6-week home-based static stretching, dynamic stretching, or eccentric exercise interventions on muscle-tendon properties and functional performance in older women - Juntip Namsawang; Wirasinee Srijunto; Phurichaya Werasirirat; Audrius Snieckus; Kristina Bradauskiene; Sigitas Kamandulis; Pornpimol Muanjai (Journal of Exercise Science & Fitness, 2024)
Background: Joint inflexibility is acknowledged as a significant contributor to functional limitations in the older adult, with lengthening-type exercises identified as a potential remedial approach. Nevertheless, the responses to eccentric exercise in female older adults have not been extensively studied especially in home-based environment. Here, we aimed to assess the effectiveness of home-based static stretching (ST), dynamic closed-chain stretching (DCS), or eccentric exercise (ECC) interventions on flexibility, musculotendinous architecture, and functional ability in healthy older women. Methods: We randomly assigned 51 healthy older women (age 65.9 ± 3.4 years) to one of three interventional exercise groups: DCS (N = 17), ECC (N = 17), or ST (N = 17). The training was performed 3 times a week for 6 weeks. The participants’ musculotendinous stiffness, fascicle length, eccentric strength, and functional capacities were measured before the intervention, after 6 weeks of exercise, and at a 1-month follow-up. Results: The results showed that all three interventions improved hamstring flexibility and passive ankle dorsiflexion (p < 0.001), with increased biceps femoris and medial gastrocnemius fascicle length (p < 0.01). However, there was no significant change in musculotendinous stiffness. The ECC intervention produced a greater improvement in knee flexor and calf eccentric peak torque (p < 0.05), and gait speed (p = 0.024) than the other two interventions. The changes in flexibility and knee flexor strength remained for up to 4 weeks after detraining. Conclusion: In conclusion, the present study suggests that home-based ECC may be more beneficial in enhancing physical capacities in older women compared with either DCS or SS interventions.